Anxiety and Depression in Adults With Congenital Heart Disease - Lebherz, Corinna; Frick, Michael; Panse, Jens; Wienstroer, Philipp; Brehmer, Katrin; Kerst, Gunter; Marx, Nikolaus; Mathiak, Klaus; Hövels-Gürich, Hedwig (Frontiers in Pediatrics, 2022)
Anxiety and depression can worsen outcome in patients with heart disease. We elucidate the prevalence of anxiety and depression in a cohort of adults with congenital heart disease (ACHD). Methods: Prospective screening for anxiety or depression was performed in 204 consecutive patients of the outpatient clinic of our tertiary care center using the Hospital Anxiety and Depression Scale (HADS) questionnaire and the distress thermometer (DT) as a potential ultra-short screening test. Functional data were assessed at liberty of the responsible physician. HADS scores ≥8 were considered doubtful and scores ≥ 11 as confirmed cases of anxiety or depression, respectively. HADS results were compared with a historical group of 100 patients with non-Hodgkin Lymphoma (NHL) as well as German reference values from the literature. Results: Patients from the ACHD cohort were 28±10 years old (Mean±SD, 54% male), 34% had a simple, 51% a moderate, including 52 patients with transposition of the great arteries after arterial switch operation, and 15% a heart defect of severe complexity. Prevalence of depression in ACHD was comparable to the German normal population (5.9% ACHD vs 5.4% control). In contrast, prevalence of anxiety was higher than expected from reference values (12.7% ACHD versus 5.6% control). There was a positive association between psychological distress and NYHA class (anxiety: OR 2.67 (95% CI; 1.50-4.76) p=0.001; depression: OR 2.93 (95% CI; 1.60-5.35) p=0.0005), but not with age, gender or heart defect severity. Percentages of ACHD patients with anxiety were significantly higher than in a cohort of patients with indolent Non-Hodgkin lymphoma (NHL) but comparable to those with aggressive NHL (HADS-A ≥ 11: ACHD 12.7%, indolent NHL 2.2%, aggressive NHL 13.2%; p=0.037 ACHD vs. indolent NHL; p= 0.929 ACHD vs. aggressive NHL). The distress thermometer screening test had only a fair discriminatory ability (AUC 0.708; p=0.002) and is therefore of limited usability. Conclusion: Adults with congenital heart disease exibit an increased risk for anxiety disorders independently of the severity of the underlying heart defect. Anxiety prevalence was comparable to a historical cohort of patients with aggressive NHL underlining the importance of a routine screening for psychosocial distress in congenital heart disease.